The Nunns celebrate 50th (Raton Range Raton, New Mexico, 1985)
Newspaper Article on the 50th Anniversary of Earl and Cora Lea Nunn.
Master list item #: 98
File location is in the Raton File Cabinet
Keywords: Nunn, Earl; Nunn, Cora Lea; Carmichael, Patsy; Nunn, Robert; Nunn, Kathleen; Carmichael, Carlton; Carmichael, Kevin; Carmichael, Kathy; Nunn, Reid; Nunn, Mickey; Nunn, Tyler; Sheraton Old Town; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Albuquerque, New Mexico; Santa Fe, New Mexico; Las Cruces, New Mexico; Alamogordo, New Mexico; Des Moines, New Mexico; Texas; Colorado